Directional fretting wear behaviour of constrained groove pressed aluminium sheet - Yadav P.C.; Gupta G.; Gupta R.; Nisar A. (My University, 2025)
Wear behavior of the constrained groove pressed (CGP) aluminium (Al) sheet was examined along both the longitudinal as well as transverse direction using fretting wear tester. The results unequivocally showed a significant diminution (up to 1.2 times for one pass) in the coefﬁcient of friction (COF) which leads to significant improvement in the wear resistance after each pass of CGP when compared to the as-received (AR) sample. Subsequently, wear rate in the CGP processed sample was found to be lower along the transverse direction (∼ 0.38 ± 0.08 ×102 µm3/N.mm) compared to that in the longitudinal direction (∼ 0.87 ± 0.12 ×102 µm3/N.mm) for one pass sample. Along longitudinal direction the major wear mechanism is discerned to be severe abrasion followed by crater formation in the samples with lower strain (i.e. 1 pass), however, it is delamination followed by dense tribolayer formation in the highly strained sample along transverse direction. Increasing fraction of oxygen content in energy dispersive spectroscopy result support the formation of dense tribolayer along transverse direction which attribute to formation of protective layer in the wear scar. The substantial decrement in the wear volume and hence wear rate after severe deformation is credited to the signiﬁcant strain imposed in the sample, which leads to significant hardness up to ∼ 1.5 times for 3 pass CGP (44.5 VHN) due to the grain refinement from AR to 3 pass CGP i.e., ∼ 21.64 µm to ∼ 5.60 µm. Therefore, effect of grain refinement on the mechanical as well as wear properties with CGP on Al substrate has also been established. © 2023 Elsevier Ltd